Development of Non-Conservative Joints in Beam Networks for Vibration Energy Flow Analysis. (2007) - Song, Jee-Hun; Hong, Suk-Yoon
Abstract : Our work aims to find a general solution for the vibrational energy flow through a plane network of beams on the basis of an energy flow analysis. A joint between two semi-infinite beams are modeled by three sets of springs and dashpots. Thus, the results can incorporate the case of complaint and non-conservative in all the three degrees of freedom. In the cases of finite coupled structures connected at a certain angle, the derived non-conservative joints and developed wave energy equation were applied. The joint properties, the frequency, the coupling angle, and the internal loss factor were changed to evaluate the proposed methods for predicting medium-to-high frequency vibrational energy and intensity distributions.